PENGARUH CAR, NPL, DAN CR PADA PROFITABILITAS BPR SE- KABUPATEN GIANYAR - Wulandari, Luh Putu Fiadevi; Sudjarni, Luh Komang (E-Jurnal Manajemen, 2014)
ABSTRACT Profitability is a financial ratio to determine the ability of banks to use its assets to make a profit. There are several variables that mepengaruhi profitability of a bank, among others, capital adequacy ratio (CAR), non-performing loans (NPL) and cash ratio (CR). This study aimed to determine the effect of capital adequacy ratio, non-performing loans and the cash ratio on profitability in rural banks (BPR) in Gianyar regency period 2008-2012. Engineering samples are used census. Multiple linear regression analysis of panel data is used as a data analysis technique. The conclusion from the testing shows the independent variable, capital adequacy ratio and the cash ratio has no effect on profitability, while the non-performing loan has a negative and significant impact on profitability. Keywords: profitability, capital adequacy ratio, non-performing loans, and cash ratio.